Implementasi Program Pareting di PAUD (KB/RA) Adinda Dua Tebel Gedangan - Aulia, Rahmita; Nugroho, Rivo (J+PLUS UNESA, 2024)
PAUD (KB/RA) Adinda Dua Tebel Gedangan is one of the PAUD institutions that has a parenting program. This research explores the implementation of the parenting program at PAUD (KB/RA) Adinda Dua Tebel Gedangan, highlighting aspects of planning, implementation and evaluation. Through qualitative methods with a participatory observation approach, in-depth interviews, and document analysis, the research results show that the parenting program in PAUD has a positive impact, increasing parents' participation and understanding of effective parenting patterns. Activities such as seminars, workshops and community events form close collaboration between institutions and families, creating a holistic educational environment. Evaluation of the program showed significant improvements in parent participation and understanding, although highlighting challenges such as logistical constraints and lack of involvement by some parents. This research makes an important contribution by detailing the factors that influence the successful implementation of parenting programs and providing recommendations for further improvement and development.